Autonomic control of skin microvessels: assessment by power spectrum of photoplethysmographic waves. - Bernardi, L; Radaelli, A; Solda, P; Coats, A; Reeder, M; Calciati, A; Garrard, C; Sleight, P (1996)
1. Although it is well known that the microvessels of the skin constantly undergo spontaneous variations in volume, the significance of these rhythmic changes remains uncertain. 2. In 10 healthy males and in 15 patients in intensive care, we assessed the origin of the autonomic influences on spontaneous fluctuations in the microcirculation of the skin, obtained by an infra-red photoplethysmographic device; we used spectral analysis techniques to compare these fluctuations (which were recorded simultaneously in two sites) with those of blood pressure, in order to test the presence of autonomic control of any synchronous fluctuations in these different measurements from the cardiovascular system. In order to minimize mechanical fluctuations caused by occasional slow breaths, rather than nervously mediated fluctuations in skin blood flow, respiration was controlled at 15 breaths/min (0.25 Hz). 3. Spontaneous infra-red photoplethysmographic fluctuations were observed in different body areas (left index finger and left ear lobe, right and left index finger), and all were evident at 0.1 Hz, as well as respiration-related components at 0.25 Hz. Active standing increased the power of the 0.1 Hz fluctuations (sympathetic activity) in both blood pressure (from 62.7 +/- 7.1 to 79.2 +/- 3.7 normalized units, P < 0.05) and IRP (finger: from 68.5 +/- 6.4 to 86.9 +/- 3.4 normalized units, P < 0.05; ear: from 59.0 +/- 5.9 to 88.1 +/- 2.0, P < 0.01). There was a high (> 0.5) coherence between the fluctuations obtained in blood pressure, in IRP signals obtained simultaneously at the finger and at the ear, and in R-R interval. This synchronization between the oscillations in all these signals, which were unrelated to the respiratory frequency or to the pulse rate, suggests a common neural, non-local origin. The phase between IRP and blood pressure was positive in the 0.1 Hz region (+1.65 +/- 0.41 radians, i.e. IRP was leading blood pressure, showing that 0.1 Hz fluctuations were not passively transmitted to the skin microvessels from large arteries) and negative in the 0.25 Hz region (-0.74 +/- 0.19 radians, P < 0.01 compared with phase in the 0.1 Hz region, i.e. IRP was lagging behind blood pressure, suggesting possible passive transmission to the skin microvessels of blood pressure fluctuations caused by respiration). Fluctuations at lower frequency were observed in all IRP recordings, suggesting a local origin for these. Intra-arterial and IRP fluctuations were compared in the 15 intensive care patients and gave similar results. 4. The skin microcirculation is thus not only under local control, but also reflects changes in sympathetic activity; the effect of these changes on the skin microcirculation can be easily evaluated by the spectral analysis of the IRP signal obtained simultaneously in multiple areas, in conjunction with the spectra of R-R interval and blood pressure.